Factors influencing public support for dairy tie stall housing in the U.S. - Robbins, Jesse A. (PLoS One, 2019)
A number of studies have shown widespread public concern over housing animals in ways that restrict their ability to move freely. Dairy cows housed in tie stall barns are tethered continuously or for part of the day, but no study has assessed public support for this type of housing system. We report two experiments assessing public perceptions of tie stall housing for dairy cattle using a hypothetical referenda format. In Experiment 1, 65% of participants (n = 430) said they would support a ban on tie stalls. The probability of supporting a ban increased as the duration of time that cows were tethered increased. In Experiment 2, information about possible economic consequences was included. Relatively fewer (55%) participants (n = 372) indicated they would support a ban. Supporters of a ban were willing to pay an average dairy product price premium of 68% to see the ban enacted. Indirect measures of support indicated socially desirable responding was greater in Experiment 2 where the economic impacts of voting behavior were made explicit. In both studies, women and liberals were more likely to support a ban. The majority of participants in Experiment 1 (51%) and Experiment 2 (57%) said they had never heard or read anything about tie stalls before participating in our survey. We conclude that current knowledge of the use of tie stalls is low, but if this situation were to change there may be considerable public concern about the use of this housing method.